ECO-DEEP AQIDAH LEARNING MODEL (EDALM): RECONSTRUCTION OF AQIDAH AND AKHLAK LEARNING BASED ON ECOTHEOLOGY AND DEEP LEARNING - Rustan Efendy; Luthfiyah Mahrusah (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to construct the Eco Deep Aqidah Learning Model, or EDALM, for Aqidah Akhlak learning in the Professional Teacher Education, or PPG, context in Indonesia. The model responds to the gap between theological understanding and ecological practice by positioning tawhid, akhlak, and environmental responsibility as values that must be reflected, interpreted, and practiced in learning. This study employed a qualitative grounded theory approach involving 15 Aqidah Akhlak PPG participants selected through purposive and snowball sampling. Data were collected through semi structured interviews, participatory observation, and documentation, then analyzed through open coding, axial coding, and selective coding. The findings generated EDALM as a substantive pedagogical model consisting of three interrelated processes: reflective theological awareness, contextual ecological interpretation, and experience based moral action. These processes explain how learners move from understanding tawhid and akhlak as normative concepts toward embodying ecological responsibility as part of religious commitment. EDALM differs from conventional Aqidah Akhlak learning by integrating eco theological reflection with deep learning mechanisms, so that learning is not limited to knowledge transmission but directed toward value internalization and transformative ecological religiosity. The study offers a conceptual and pedagogical basis for strengthening ecological awareness in Islamic teacher education. However, the model was developed within the specific context of Aqidah Akhlak PPG participants and therefore requires further validation in broader educational settings. This study contributes a grounded model of Aqidah Akhlak learning in the PPG context by operationalizing the relationship between Islamic eco theology, deep learning, and ecological value internalization. Its originality lies not in claiming that eco theology and deep learning are entirely new discourses, but in formulating an empirically grounded model that connects these concepts within a structured Islamic teacher education framework.